Patriotric Progress - Rak, Jiří (Dějiny – teorie – kritika, 2009)
Using a series of examples, the author reflects on the mutual determination of the general idea of progress and the phenomenon of the ‘National Awakening’ with the economic and cultural emancipation of the Czech nation through the eyes of actors in this process. Employing their frequently used term ‘national progress’, he also demonstrates their inner tensions, reservations about the universal ‘religion of progress’, and the meaning of their conservative elements. In the ironic framework of Jaroslav Hašek’s ‘Party of Moderate Progress within the Bounds of the Law’, he also finds pertinent shorthand with which to explain the Bohemian National Awakeners’ understanding of progress.